The impact of restructurization on organizational performance (case study on Educational Quality Assurance Institution, Central Java, Indonesia) - Triastuti, Nugraheni; Putranti, Ika Riswanti; Yuniningsih, Tri; Purnaweni, Hartuti (Management and Entrepreneurship: Trends of Development, 2023)
Changes in the organizational structure of the Central Java LPMP can be seen from the very wide span of control because there is only one leader controlling 148 employees. The change in organizational structure at the Central Java LPMP was due to the simplification of the bureaucracy through the conversion of administrative employees into functional employees. The study is aimed at profound explaining of the restructuring impact on the overall performance of the organization namely LPMP Central Java. The researchers interviewed 6 informants that is: Head of Central Java LPMP, Head of Organization Bureau and Governance Kemdikbudristek, Head of HR Bureau Kemdikbudristek, Head Deputy Empowerment of HR Apparatus KemenPAN-RB, and Central Java LPMP employees. Besides, researchers also analyze the activity of the employee and the leader while carrying out the restructuring process. As a result, organizational changes resulting from bureaucratic simplification in the Central Java LPMP bring to a shift in the hierarchical system. There is a special team or tough team that was deliberately formed to achieve the organizational performance targets of the Central Java LPMP. The impact is that organizational performance has increased as proven in the LPMP Central Java Government Agency Performance Report (LAKIP) with good results. The 2021 Central Java Province LPMP performance report presents the achievement of two activity targets with five performance indicators as stated in the 2021 Performance Agreement document. The research results also envisage the existence of organizational values that are instilled in its employees. JEL Classification: O380, O31, O330